UNIVERSITY EXTENSION ACTIVITIES IN PHARMACY: HEALTH PROMOTION AND ACADEMIC TRAINING (CIPEEX, 2026)
ABSTRACTINTRODUCTION: University extension, a pillar of higher education alongside teaching and research, brings the university closer to society and qualifies health education. In the Pharmacy course, low-cost and wide-reaching community actions promote prevention and health education, especially regarding Noncommunicable Diseases (NCDs), such as hypertension and diabetes. OBJECTIVE: To describe the impact of Extension Activities, carried out by pharmacy students, on the consolidation of theoretical knowledge. METHODS: Descriptive/qualitative experience report concerning approximately 23 actions carried out by Pharmacy students under faculty supervision, in public squares, partner pharmacies, and itinerant events. Each action involved an average of twelve student volunteers and offered pharmaceutical services such as: blood pressure measurement, capillary blood glucose testing, and blood typing, in addition to guidance on prevention and the rational use of medicines. RESULTS: These low-cost and wide-reaching practices enabled direct benefits to the community, by favoring the early identification of risks for systemic arterial hypertension and diabetes, in addition to encouraging preventive awareness. For the students, the experience was fundamental in technical development, in closer contact with social reality, and in the construction of humanized competencies, reinforcing the relevance of extension as a link between university and society. CONCLUSION: The results collected during the actions reinforce how important the role of the pharmacist is in society, as an accessible and reliable public health figure. It is important to emphasize that the extension activities in Pharmacy showed relevant social impact and pedagogical potential, consolidating extension as a link between university and society and reaffirming the pharmacist as an accessible professional in collective health care.Keywords: University extension; Pharmacy; Health promotion; Pharmaceutical care.